Transcriptomics reveals the underlying mechanism of Prostaglandin E1 in improving severe pneumonia - Wentong Ma; Jingxin Zhou; Ying Qian; Su Zhang; Chuanlu Han; Jing Su; Haijun Sun (BMC Pulmonary Medicine)
Abstract Background Severe pneumonia is a lung parenchymal inflammation that can lead to multi-organ failure and death. Prostaglandin E1 (PGE1) is an autoreactive substance with extensive physiologic and pharmacologic properties. This study aims to investigate the ameliorative effect and potential mechanism of PGE1 in mice with severe pneumonia. Methods Mouse models of severe pneumonia were established by lipopolysaccharide (LPS), and the mice were administrated PGE1 to observe the effects of PGE1 on the pathological injury of lung tissues, wet-to-dry weight (W/D) ratio of lung tissues, levels of inflammatory factors in broncho-alveolar lavage fluid (BALF) and lung tissues, the number of white blood counts (WBCs) and polymorphonuclear neutrophils (PMNs) in BALF, blood gas indexes, and Th17/Treg balance. The critical signaling pathways of PGE1 involved in severe pneumonia were obtained by transcriptome sequencing (RNA-seq), and the regulatory role of PGE1 in alleviating severe pneumonia was observed by the JAK inhibitor AG490. Results PGE1 can alleviate lung histopathological injury in mice with severe pneumonia, decrease W/D ratio, attenuate interleukin- 1β (IL-1β), interleukin- 6 (IL-6), and tumor necrosis factor-α (TNF-α) levels, increase interleukin- 10 (IL-10) levels in mouse BALF and lung tissues, and reduce the number of WBCs and PMNs; it can increase the arterial blood partial pressure of oxygen (PaO2) and decrease the arterial blood partial pressure of carbon dioxide (PaCO2), and up-regulate the proportion of Treg cells, decrease RORγt expression, and increase Foxp3 expression. Differential gene expression analysis and enrichment analyses showed that the enrichment of JAK-STAT pathway was decreased in the LPS + PGE1 group compared to the LPS group. Joint use of PGE1 and AG490 can reduce p-JAK2 and p-STAT3 protein expression and synergistically improve the pathological damage phenotype in mice with severe pneumonia. Conclusion PGE1 can alleviate lung histopathological injury and reduce the degree of pulmonary edema in mice with severe pneumonia, and the mechanism might be realized by preventing PMN aggregation and activation in the lungs, reducing the release of inflammatory mediators, improving pulmonary ventilation, and regulating immune homeostasis. Moreover, by using transcriptome analysis and animal experiments, this study found that PGE1 participates in severe pneumonia by regulating JAK-STAT pathway.